The influence of sustainability reporting and green accounting on financial performance of mining companies listed on the Indonesia stock exchange for the 2021-2023 period - Anik Viati Solehah; Selly Puspita Sari; Fitria Fertha Agustina (Institute of Accounting Research and Novation (IARN), 2025)
This study aims to analyze the influence of sustainability reporting and green accounting on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Sustainability reporting is measured using the Corporate Social Responsibility (CSR) disclosure index, while green accounting is proxied by the PROPER rating issued by the Ministry of Environment and Forestry. Financial performance is proxied by Return on Assets (ROA). This research employs a quantitative approach using multiple linear regression analysis, processed with SPSS version 23. The sample was selected through purposive sampling from a population of 83 companies, resulting in 22 companies that met the criteria over the three-year observation period, yielding a total of 66 data points. The findings reveal that sustainability reporting has a positive and significant effect on financial performance. Similarly, green accounting also has a positive impact on the company’s financial performance. These findings support stakeholder theory and legitimacy theory, which posit that transparency and concern for social and environmental aspects can enhance stakeholder legitimacy and trust, ultimately improving a company’s financial performance. This study offers important implications for companies, investors, and policymakers in promoting sustainable business practices.